Assessment of Surgeon Variation in Adherence to Evidence-Based Recommendations for Treatment of Trigger Finger - Billig, Jessica I. (JAMA Netw Open, 2019)
IMPORTANCE: Stenosing tenosynovitis (trigger finger) affects approximately 2% of the population. Given the prevalence of trigger finger and rising health care costs, adherence to the cost-effective and evidence-based treatment algorithm will permit better outcomes and allocation of resources. OBJECTIVES: To examine treatment patterns for trigger finger and to determine surgeon-level and patient-level factors that influence adherence to evidence-based treatment. DESIGN, SETTING, AND PARTICIPANTS: This retrospective population-based cohort study examined deidentified claims for treatment of trigger finger from a national insurance provider using the Clinformatics Data Mart database. Patients were included if they were 18 years or older and treated from January 1, 2002, through December 31, 2016 (excluding a washout period from July 1, 2008, until June 30, 2010), with a new diagnosis of single-digit trigger finger. Data were analyzed from December 21, 2018, through April 28, 2019. EXPOSURES: Cost-effective and evidence-based research published in July 2009 for the treatment of trigger finger. MAIN OUTCOMES AND MEASURES: After excluding the 1-year washout period on either side of July 1, 2009, adherence to the recommended treatment algorithm of 2 corticosteroid injections before surgical release of trigger finger was compared with practice before publication of research supporting this cost-effective and evidence-based approach. RESULTS: In this analysis of 83 667 patients with trigger finger, 52 698 (63.0%) were women, and 20 045 (24.0%) had type 1 or 2 diabetes. Mean (SD) age was 61 (13) years. From 2002 to 2016, an overall increasing trend in adherence to the cost-effective and evidence-based approach to treatment was noted, with no significant increase in adherence in the postpublication era (67.5% vs 73.3%; P = .27). Substantial variation in adherence was observed at the surgeon level (intraclass correlation, 33%). Plastic surgeons had no change in adherence over time compared with orthopedic surgeons (odds ratio [OR], 1.00; 95% CI, 0.98-1.02; P = .90), whereas general surgeons had increased adherence (OR, 1.04; 95% CI, 1.02-1.06; P < .001). Higher-volume surgeons were also more adherent to these evidence-based recommendations (OR, 1.59; 95% CI, 1.53-1.65; P < .001). CONCLUSIONS AND RELEVANCE: This study found substantial surgeon-level variation in adherence to evidence-based treatment of trigger finger. Surgeon specialty and volume were associated with differences in adherence. Efforts to understand surgeon barriers to implementation, regardless of physician specialty, appear to be necessary, and better implementation strategies may permit increased uptake of evidence-based treatment of trigger finger.